Instability-Associated Changes in Contact Stress and Contact Stress Rates in Human Cadaveric Ankles - McKinley, Todd O. (2008)
BACKGROUND: Intra-articular fractures can result in articular surface incongruity and joint instability, both of which can lead to post-traumatic osteoarthritis. The purpose of this study was to quantify changes in contact stresses and contact stress rates in incongruous human cadaveric ankles that were either stable or unstable. It was hypothesized that joint instability, superimposed on articular incongruity, would cause significant increases in contact stresses and contact stress rates. METHODS: Intact human cadaveric ankles were subjected to quasi-physiologic stance-phase motion and loading and instantaneous contact stresses were captured at 132 Hz. The anterior one-third of the distal tibia was displaced proximally by 2.0 mm, and testing was repeated. Anterior/posterior forces were modulated during loading to cause incongruous ankles to either remain stable or become unstable during loading. Transient contact stresses and contact stress rates were measured for seven ankles under intact, stable-incongruous, and unstable-incongruous conditions. Peak and 95(th) percentile values of contact stress and contact stress rates for all three conditions were compared using paired t-tests to determine the pathomechanical effects incongruity and instability. RESULTS: The addition of instability caused 95(th) percentile and peak contact stresses to increase between 20% and 25% in unstable-incongruous specimens compared to stable-incongruous specimens. In contrast, the addition of instability increased the magnitude of peak positive and peak negative contact stress rates by 115% to 170% in unstable-incongruous specimens compared to stable incongruous specimens. Likewise, 95(th) percentile contact stress rates increased 112% in unstable-incongruous specimens compared to stable-incongruous specimens. CONCLUSIONS: In incongruous human cadaveric ankles, instability superimposed on an existing articular surface incongruity caused disproportionate increases in contact stress rates compared to increases in contact stresses. CLINICAL RELEVANCE: Cartilage injury, chondrocyte injury, and chondrocyte biosynthetic function have been shown to be particularly sensitive to stress rate. Instability-associated increases in contact stress rates may be important pathomechanical factors that lead to post-traumatic osteoarthritis.